Drugs increase the risk of suicide in the elderly - Kędziora-Kornatowska, Kornelia; Winiarek, Karolina; Murawska, Joanna; Mikut, Karolina; Kwiecień, Justyna; Wijata, Aleksandra; Al-Shaer, Aysheh (Journal of Education, Health and Sport, 2022)
The purpose of this paper is a systematic review of articles and research in the context of drugs used and suicide in elderly patients. Suicide in the elderly may be much more frequent than in the younger population. In addition to factors such as mental illness, dementia, deteriorating health, or problems with adapting to old age, the impact of chronic and reliever medications in this age group should also be considered. The greatest challenge of pharmacotherapy in the elderly is polypharmacy, drug interactions, different metabolism, pharmacokinetics and pharmacodynamics of the drugs used, as well as the side effects appearing in chronic therapy. In elderly patients, strong groups of drugs such as benzodiazepines and opioids are used extensively and sometimes too often. These drugs can cause addiction and overdose. Prescribing benzodiazepines alone carries a high risk of suicide. On the other hand, opioids often lead to addiction and abuse of these drugs, which may be associated with the development of respiratory depression. According to estimates by the Centers for Disease Control and Prevention (CDC), suicide accounts for approximately 7% of all opioid overdose deaths. Therapy should be carefully selected with regard to the use of other medications, drug interactions, and possible dependence and drug abuse by patients.The use of some classes of drugs in the elderly requires increased vigilance and control in the context of depression and episodes of suicide attempts. Drugs such as B blockers, digitalis glycosides, NSAIDs, opioids, ACEIs, calcium channel blockers, corticosteroids, diuretics, levodopa, and benzodiazepines can cause symptoms of depression. Older people are more susceptible to side effects of drugs, for example because of polypharmacy and the chronicity of treatment.